Evaluasi Risiko Ergonomi pada Aktivitas Kerja Pekerja di Pabrik Keripik Singkong Sari Asih Menggunakan Metode Rapid Entire Body Assessment (REBA) - Zein Aurelia Cabrine; Totok Pujianto; Koko Iwan Agus Kurniawan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The Sari Asih Cassava Chips Factory is still dominated by manual work activities that may pose ergonomic risks due to non-ergonomic working postures. This study aimed to evaluate workers' ergonomic risks using the Rapid Entire Body Assessment (REBA) method. An observational study was conducted involving five workers from the frying, chopping, and seasoning workstations through direct observation, anthropometric measurements, the Nordic Body Map (NBM) questionnaire, and REBA analysis. The results indicated that workers experienced musculoskeletal complaints with REBA scores of 6 (moderate risk), 8 and 10 (high risk), and 11 (very high risk). The ergonomic risks were primarily associated with bent working postures, repetitive movements, and prolonged static positions. Therefore, improvements in working postures and work facilities tailored to workers' characteristics are necessary to reduce the risk of musculoskeletal disorders while enhancing occupational comfort, safety, and productivity throughout the production process.